Design of a Monitoring System for Hydroganics based on Arduino Uno R3 to Realize Sustainable Development Goal`s number 2 Zero Hunger - Anggara Trisna Nugraha; Dadang Priyambodo (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2021)
In 2019 Indonesia is able to support its nation and does not need rice imports from abroad. This situation is called rice self-sufficiency. Then in order to maintain rice self-sufficiency from year to year, it is necessary to apply technology to increase the quality of rice production. Therefore, a Hydroganic Monitoring System Design was created which is used to monitor plant watering automatically using the YL-69 soil moisture sensor controlled by Arduino Uno and instructed to the LCD to display the soil moisture value according to soil pH in real time. The watering system that has been created can automatically drain water to the plants. The water that is flowed automatically by this system comes from the fish pond that is right below it, where the water from fish excrement will produce organic nutrients for rice plants. With this research, rice production will grow more effectively to improve rice quality. With this research, it is expected that Indonesian rice production will increase effectively and in line with the improvement of rice quality. From the research that has been conducted, it is found that from the experimental data above, it can be calculated that the average water discharge in one irrigation is 2.37 m/s.